Anatomic and Physiological Bases of Social Blushing: Speculations from Neurology and Psychology - W. D. Cutlip II; M. R. Leary (Behavioural Neurology)
Although a common and occasionally troubling reaction, social blushing has received little systematic attention from either medical or behavioral researchers. This article reviews what is known of the physiological and psychological processes that mediate social blushing, and speculates regarding the role of central mechanisms in the phenomenon. Blushing is characterized by the unusual combination of cutaneous vasodilatation of the face, neck, and ears, accompanied by activation of the sympathetic nervous system. Psychologically, blushing appears to occur when people receive undesired social attention from others and may be analogous to the appeasement displays observed in non-human primates. Although poorly understood, the central mechanisms that mediate blushing obviously involve both involuntary autonomic effector systems and higher areas that involve self-reflective thought. Questions for future research are suggested.